A Sequential Concession Game with Asymmetric Information - Ordover, Janusz A.; Rubinstein, Ariel (Quarterly Journal of Economics, 1986)
Janusz A. Ordover, Ariel Rubinstein; A Sequential Concession Game with Asymmetric Information*, The Quarterly Journal of Economics, Volume 101, Issue 4, 1 Novem